An examination of the extent of legislative power in annual fiscal budget making in Nigeria (2019)
This paper examines the perennial tussle between the executive and legislative arm of government in Nigeria in relation to budget making, which sometimes leads to delay in passage of annual fiscal budget. The extent of powers to be exercised by the Legislature in amending budget estimates submitted by the Executive is the crux of the dispute which often leads to diverse and conflicting opinions on whether the law permits the Legislature to tamper with the figures of the budget or whether it should be a mere rubber stamp to approve the estimated budget submitted to it by the Executive. The paper reviews the changing role of the Legislature in modern times, particularly in the presidential system of government and the involvement of the public ably represented by civil society organisations in determining financial policies that will drive annual budgets. The paper submits that due to absence of clear provisions of the law to determine the extent of powers of the Legislature to amend budgets, it may be necessary to amend the Constitution to clearly define the scope of the power of the Executive and the Legislature in budget making.